The unknown house of an old neighbor: the nest of Zethus (Zethoides) nodosus Zavattari (Hymenoptera: Vespidae) - Lopes, Rogério Botion [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
Despite being mostly solitary and nesting in cavities, Zethus is more widely known by its few representatives that build external aerial nests. Here, nests of Zethus nodosus collected in the first decades of the twentieth century in surrounding areas of the Museu de Zoologia da Universidade de São Paulo are described and ponderations about the absence of more recent material are made.
Keywords: Habitat loss; Nest architecture; Zethus olmecus species group